The geology, geochemistry and stratigraphic correlations of the farm Rietfontein 70 JS on the south -eastern flank of the Dennilton Dome, Transvaal, South Africa - Crous, Stephanus Philippus (Rhodes University, Faculty of Science, Department of Geology, 1996)
The study area is located between Loskop Dam and the town of Groblersdal, on the southeastern flank of the Dennilton dome, and is underlain by lithologies of the Pretoria Group, Bushveld Complex mafics and ultramafics and acid lavas that resort under the Rooiberg felsites. Field work comprised of geological mapping, soil-, hard-rock- and stream sediment geochemistry, various geophysical techniques and diamond drilling. The rocktypes that resembles the Rustenburg Layered Suite on the farm Rietfontein 70JS is subdivided into a Mixed Zone, Critical Zone and Main Zone, on grounds of geochemical and certain geophysical attributes. The Mixed Zone that overlies the Bushveld Complex floor-rocks, is furthermore separated into an i) Lower-, ii) Middle- and, iii) Upper Unit. The Lower Unit of the Mixed Zone consists primarily of magnetite-gabbros, iron-rich pegmatites, harzburgites and feldspathic pyroxenites. The Fe-rich constituents of this stratigraphic horizon generates a pronounced magnetic anomaly within the study area. On the basis of; amongst other parameters, Zr/Rb and Sr/Alâ‚‚0â‚ƒ ratios, the magnetite-gabbros are postulated to conform to lithotypes in the vicinity of magnetite layers 8 to 14 of Upper Zone Subzone B in a normal Bushveld Complex stratigraphical scenario. Similarly, it is argued that the feldspathic pyroxenites and norites that display elevated chromium values are analogues to normal Critical Zone rocktypes of the Rustenburg Layered Snite. A more elaborate and precise stratigraphic correlation for the Critical zone was, however, not possible. It is advocated that a volume imbalance was created by the hot, ascending mafic magmas of the intruding Bushveld Complex, resulting in the updoming of certain prevailing basement features such as the Dennilton Dome. In addition to this ideology, it is proposed that the Mineral Range Fragment is in fact a large xenolith underlain by mafics, after being detached from the Dennilton Dome during the intrusion event. Evidence generated by this study unequivocally indicate that the potential for viable PGE's, Ni, Cu and Au within a Merensky Reef- type configuration or a Plat Reef-type scenario under a relatively thin veneer of acid Bushveld Complex roof-rocks on the eastern flank of the Dennilton Dome, appears feasible.
Keywords: Stratigraphic correlation -- South Africa -- Transvaal; Geology, Stratigraphic; Geochemistry -- South Africa -- Transvaal; Geology -- South Africa -- Transvaal